2014
DOI: 10.1136/annrheumdis-2013-204761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiographic and immunogenic effects after 1 year of tocilizumab-based treatment strategies in rheumatoid arthritis: the ACT-RAY study

Abstract: ObjectiveTo assess the 1-year efficacy and safety of a regimen of tocilizumab plus methotrexate or placebo, which was augmented by a treat-to-target strategy from week 24.MethodsACT-RAY was a double-blind, 3-year trial. Adults with active rheumatoid arthritis despite methotrexate were randomised to add tocilizumab to ongoing methotrexate (add-on strategy) or to switch to tocilizumab plus placebo (switch strategy). Tocilizumab 8 mg/kg was administered every 4 weeks. Conventional open-label disease-modifying ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
5

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 22 publications
3
87
0
5
Order By: Relevance
“…The radiographic progression was defined as any change in GSS > the smallest detectable change (SDC) computed based on the difference between the x-ray readers. The results showed that the overall radiographic progression was small in both groups although it was statistically significant (add-on therapy versus switch to monotherapy); 8% and 14% respectively [46].…”
Section: Effect On Radiographic Progressionmentioning
confidence: 92%
See 1 more Smart Citation
“…The radiographic progression was defined as any change in GSS > the smallest detectable change (SDC) computed based on the difference between the x-ray readers. The results showed that the overall radiographic progression was small in both groups although it was statistically significant (add-on therapy versus switch to monotherapy); 8% and 14% respectively [46].…”
Section: Effect On Radiographic Progressionmentioning
confidence: 92%
“…This was done over a 2 year period in patients who had an inadequate response to methotrexate (MTX-IR). The results are now available at 52 weeks [46]. 556 patients were randomly assigned either to continue methotrexate with the addition of tocilizumab 8 mg/kg 4-weekly or switch to tocilizumab monotherapy.…”
Section: The Ambition (Actemra Versus Methotrexate Double-blindmentioning
confidence: 99%
“…ACT‐RAY was a 3‐year, double‐blind, placebo‐controlled, parallel‐group clinical trial (NCT00810199) 3, 4. Briefly, eligible patients had active RA with DAS28 using the erythrocyte sedimentation rate (ESR) of >4.4 at baseline, and received methotrexate (MTX) for ≥12 weeks, with a stable dosage of ≥15 mg/week.…”
Section: Methodsmentioning
confidence: 99%
“…Two specific phases of the ACT‐RAY study offer a unique opportunity to investigate relevant aspects of flares: 1) assessment of the flare rate (according to published criteria [2]) between weeks 24 and 52, during which a large patient subgroup received constant treatment 3, 4, and 2) comparison (using sensitivity and specificity) of the flare criteria implicitly used by the investigators with published criteria 2 in the second year, during which patients reaching sustained DAS28 remission discontinued tocilizumab (TCZ) and subsequently other treatments, which were re‐started after investigators diagnosed a disease flare based on their clinical judgment.…”
Section: Introductionmentioning
confidence: 99%
“…The first one was the ACT-RAY study, which reported a comparison between TCZ and TCZ+MTX. The data suggest that both TCZ add-on and switch strategies led to meaningful clinical and radiographic responses, despite a trend favoring the add-on strategy [8]. The second was the SURPRISE study.…”
Section: Introductionmentioning
confidence: 99%